Golkar party’s utilization of TikTok for the 2024 election campaign - Pradana, Yudhis Salvania; Mirawati, Ira; Octavianti, Meria (Manajemen Komunikasi, 2023)
The successful political communication between politicians and the general public demands the utilization of social media, including TikTok, which is currently being utilized by the Golkar Party in preparation for the 2024 elections. This article examines the strategies of political communication in utilizing social media as a means of a political campaign, along with the potential opportunities and challenges that arise during the campaign. This research employs a qualitative descriptive method, collecting primary data through interviews with informants from the Golkar responsible for managing their official TikTok account. The research was conducted from October 2022 to January 2023. The results show that the utilization of TikTok by the Golkar as a campaign platform is driven by several reasons, including adaptation to reach the younger generation, leveraging TikTok’s unique features and wide reach, alignment between party leadership and team enthusiasm, expanding efforts towards democratic campaigns, and being a pioneer among political parties in TikTok utilization. This process involves audience acquisition, content direction, and human resource management. Planning the target audience and message, content design, key messages, and audience interaction are crucial aspects. The experience of Golkar can serve as an example of utilizing TikTok in politics. Challenges faced include content direction, staying up-to-date, consistency, software proficiency, and consolidating the user base.